Ángel Rosenblat, Buenas y malas palabras en el castellano de Venezuela. Prólogo de Mariano Picón-Salas. Ediciones Edime, Caracas-Madrid, 1956. 488 pp. - Speratti-Piñero, Emma Susana (El Colegio de México, 1957)
Se reseñó el libro: Buenas y malas palabras en el castellano de Venezuela. Prólogo de Mariano Picón-Salas.